Institutions and the Location Decisions of Highly Skilled Migrants to Europe - Klaus Nowotny (WWWforEurope, 2015)
This paper investigates the economic, labor market and institutional factors that make regions and countries attractive for highly skilled migrants vis-`a-vis lowskill migrants. Based on micro-data for 11 EU countries, a discrete choice model estimated at the NUTS-2 level shows that location decisions are not only determined by factors related to earnings opportunities, distance, networks, common language and colonial relationships, but also by institutional factors such as migration policy, the income tax system, or labor market institutions; it also lends some support to the welfare magnet hypothesis: a higher unemployment replacement rate increases the attractiveness of a country. The empirical analysis however reveals only minor differences in the effects of institutions on location decisions by skill level, limiting the scope for policy makers to affect the skill composition of migration.
Keywords: F22; R23; C35; 330; Highly skilled migration; regional location decisions; institutions; migration policy